2019
DOI: 10.1002/esp.4709
|View full text |Cite
|
Sign up to set email alerts
|

Drivers of island beach evolution: insights from an island‐scale study at Boa Vista (Cabo Verde)

Abstract: Beach erosion poses significant threat to small island economies which are generally highly dependent on coastal tourism. This work investigates the evolution of the low‐lying sandy coast of Boa Vista through an integrated characterization of coastline and shoreline indicators (over the past four decades) based on aerial imagery. It was found that tandem use of the two indicators was important to obtain a reliable perspective of the Boa Vista low‐lying coastal evolution across a wide range of coastal environme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Awange et al [88] indicated more erosion along the Liberian coast between 1998 and 2002. In addition, Gomes et al [89] highlighted the stable state of the Boavista, Cape Verde shoreline between 1968 and 2010. In addition, Thior et al [70] stated that the northern lower, Casamance, Senegal, and the southern beaches in Gambia accreted between 1968 and 1986, while higher erosion was observed between 1986 and 2004.…”
Section: Shoreline Change and Coastal Erosion Due To Natural Eventsmentioning
confidence: 99%
“…Awange et al [88] indicated more erosion along the Liberian coast between 1998 and 2002. In addition, Gomes et al [89] highlighted the stable state of the Boavista, Cape Verde shoreline between 1968 and 2010. In addition, Thior et al [70] stated that the northern lower, Casamance, Senegal, and the southern beaches in Gambia accreted between 1968 and 1986, while higher erosion was observed between 1986 and 2004.…”
Section: Shoreline Change and Coastal Erosion Due To Natural Eventsmentioning
confidence: 99%